Monetary policy and risk taking - Ignazio Angeloni; Ester Faia; Marco Lo Duca (Bruegel, 2011)
We assess, through VAR evidence, the effects of monetary policy on banks' risk exposure and find the presence of a risk-taking channel. A model combining fragile banks prone to risk mis-incentives and credit constrained firms, whose collateral fluctuations generate a balance sheet channel, is used to rationalize the evidence. A monetary expansion increases bank leverage. With two consequences: on the one side this exacerbates risk exposure; on the other, the risk spiral depresses output, therefore dampening the conventional amplification effect of the financial accelerator.
Keywords: 330; monetary policy; bank behavior; leverage; financial accelerator